Impact of management practices on the income of transmigrant farmers in Wonosari, Gorontalo - Amelia Murtisari; Irham Irham; Agustinus Moonti; Rahmatiah Rahmatiah; Nurdin Nurdin; Pipit Sartika; Happy Amanda Delicia Rahmanto (Agriekonomika, 2024)
The transmigration program aims to improve welfare, mainly through wet rice farming. This research objectives are: 1) To analyze the management of wet rice farming in transmigration areas; 2) To analyze the income of wet rice farming in transmigration areas; and 3) To analyze the influence of management and other factors on the income of wet rice farmers in transmigration areas. A quantitative descriptive research method was employed, with sampling conducted through purposive sampling. The study identified two management models used by wet rice farmers. Model 1 employed the jajar legowo planting pattern, utilizing irrigation and labor from within and outside the family. Model 2 applied the tabela planting pattern, relying on both irrigation and borehole irrigation, and predominantly employs labor from outside the family. The average income of rice farmers in Model 1 was IDR 3,278,446.21 per planting cycle, while in Model 2, it was IDR 1,797,150.33. Factors affecting the household income of transmigrant wet-rice farmers include age, education, land area, and farm management model.